Concurrent changes in sleep and cognitive function during retirement transition: the Finnish retirement and aging study - Teräs, Tea; Myllyntausta, Saana; Pentti, Jaana; Pasanen, Jesse; Rovio, Suvi; Stenholm, Sari (Springer Science and Business Media LLC, 2026)
The transition to retirement has been shown to be accompanied by increased sleep duration and improved sleep quality. In addition, some studies suggest accelerated decline in cognitive function in post-retirement years. However, less is known about their interconnectedness. The aim of this study was to examine the concurrent changes in sleep and cognitive function during retirement transition. The study population consisted of 250 public sector workers (mean age before retirement 63.1 years, standard deviation 1.4) from the Finnish Retirement and Aging study. The participants used a wrist-worn ActiGraph accelerometer, responded to the Jenkins Sleep Problem Scale and underwent cognitive testing annually before and after retirement. Computerized Cambridge Neuropsychological Test Automated Battery (CANTAB®) was used to evaluate learning and memory, working memory, sustained attention and information processing, executive function and cognitive flexibility, and reaction time. Cognitive function improved in all cognitive domains, except for reaction time, during 1-year retirement transition period. The improvement was temporary in learning and memory, working memory and executive function and cognitive flexibility, which plateaued in post-retirement years. The participants were categorized into constantly short (49%), increasing (20%), decreasing (6%), and constantly mid-range (25%) sleep duration; and constantly without (36%), increasing (10%), decreasing (16%), and constantly with (38%) sleep difficulties. There were no associations between changes in sleep duration or sleep difficulties and cognitive function during retirement transition. Cognitive function improves temporarily during transition to retirement, but the improvement is independent of changes in sleep characteristics.